pegegog 2023
DOI: 10.47750/pegegog.13.02.15
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Inclusive Education for Students with Hearing Impairment

Abstract: The realization of equitable and quality education has long been the central challenge in education development. The presence of inclusive education is expected to enhance those two aspects of education. Further, it is also hoped to bring an equal education for all children, including children with special needs. In developed nations, inclusive education has been implemented widely, enabling children with special needs to have greater opportunities to enroll in local schools. This study aims to explore the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Damri, et al (2023) the influences of their research revealed the influence of the principal's oversight, the principal's leadership personality, a facilitative environment, and pupil learning stimulation on the effectiveness of the learning method at SMA Negeri 6 Padang. Sinta, et al (2023) with their research revealed that the success of inclusive schooling is determined by strong inclusive cultural factors. Apart from that, the role of schools in determining policies and parents is very influential for the sustainability of inclusive education for their children.…”
Section: Introductionmentioning
confidence: 99%
“…Damri, et al (2023) the influences of their research revealed the influence of the principal's oversight, the principal's leadership personality, a facilitative environment, and pupil learning stimulation on the effectiveness of the learning method at SMA Negeri 6 Padang. Sinta, et al (2023) with their research revealed that the success of inclusive schooling is determined by strong inclusive cultural factors. Apart from that, the role of schools in determining policies and parents is very influential for the sustainability of inclusive education for their children.…”
Section: Introductionmentioning
confidence: 99%